Quality of Life of Patients with Arrhythmia - Chloubová, Ivana; Bulava, Alan (Acta Medicinae et Sociologica, 2020)
Introduction: Quality of life must be perceived in two levels - objective and subjective. Heart arrhythmia is a disease of the cardiovascular system that, by its subjective and objective symptoms, can affect the individual's life physically, mentally, and also socially. It can limit a person in his or her everyday activities or in activities that make them happy or satisfied.Objectives: The aim of the research was to map the quality of life of patients with arrhythmia and to verify whether the duration of arrhythmia has an effect on the quality of life of patients with arrhythmia.Methods: A standardized ASTA (Arrhythmia - Specific Questionnaire in Tachycardia and Arrhythmias) questionnaire was used to collect quantitative data. The research group consisted of adult patients diagnosed with hearth arrhythmia, hospitalized at the Department of Cardiology of the Ceske Budejovice Hospital (Nemocnice České Budějovice a.s.). A total of 127 valid questionnaires were used for data processing.Results: The research revealed that the most common symptom of arrhythmia in 58% cases was rapid heartbeat, irregular heartbeat, and a sense of heart failure. Most respondents agreed with the claim that heart rhythm disorder makes it impossible for them to perform work, study, and perform daily life activities. No statistically significant differences were found in the evaluation of the influence of the arrhythmia duration on the patients' quality of life.Conclusions: Arrhythmia duration in the selected sample does not affect the overall health status and quality of life measured by the ASTA series questionnaires. Arrhythmia restricts the patient to perform work tasks, study, and perform daily life activities.